PREVALENCE OF RAISED INTRAOCULAR PRESSURE IN POST CATARACT SURGERY FOLLOWING TOPICAL STEROID USAGE-A CROSS SECTIONAL STUDY - Kumar Arun, Jain Ritu (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Cataract is the leading cause of blindness globally, and cataract surgery withintraocular lens implantation is the definitive treatment. Postoperatively, topicalcorticosteroids are frequently prescribed to control inflammation, but they may induce a risein intraocular pressure (IOP), posing a risk of secondary glaucoma. Aim: To assess the prevalence of raised IOP following topical steroid usage afteruncomplicated cataract surgery and to categorize patients based on steroid response.